Retrospective study characterizing yield and physiological changes in sorghum crop - Demarco, Paula Andrea (Kansas State University, 2021)
Understanding physiological changes in response to long-term selection for yield can inform breeding decisions and hasten genetic gain. This dissertation is organized into four chapters: Chapter 1, Introduction, Chapter 2, presents yield gain achieved for US sorghum hybrids and their components (grain number and grain weight), Chapter 3 focuses on nutrient use efficiency, specifically on nitrogen (N) internal efficiency (NIE, yield to N uptake ratio), and Chapter 4, Conclusions. For Chapters 2 and 3, field trials were conducted during the 2018 and 2019 seasons in eight site-years across the states of Kansas and Texas (US) including 20 commercially available grain sorghum hybrids released by Pioneer between 1963 and 2017. Consistent with estimates using historical yield data, sorghum yield improvement was 27 kg ha⁻¹ yr⁻¹. Grain number increased at a rate of 100 grains mˉ² yr⁻¹, and modern hybrids had larger panicle size with greater accumulation of WSC during the vegetative period (until flowering). Additionally, greater remobilization of WSC during the reproductive period (after flowering) to grain was captured, thus, maintaining grain size on the increased grain number per unit area and harvest index (Chapter 2). The N internal efficiency (NIE, yield to N uptake ratio) increased at the expense of a reduction in grain N concentration and, in minor proportion, due to an increase in the N harvest index (NHI) at maturity for newer relative to older hybrids. Newer genotypes evidenced greater N remobilization from the stover to the grains during the reproductive period (Chapter 3). This study demonstrates the physiological foundations for yield enhancement and the N and C utilization behind yield genetic gain for sorghum hybrids. Future yield gains in sorghum can be pursued by enhancing N uptake to sustain further genetic progress.
Keywords: Sorghum; Yield gain; Yield components; Nitrogen; Carbohydrates; Crop physiology